Effects of winning cues and relative payout on choice between simulated slot machines. (25th March 2020) - Spetch, Marcia L.; Madan, Christopher R.; Liu, Yang S.; Ludvig, Elliot A.
Abstract: Background and aims: Cues associated with winning may encourage gambling. We assessed the effects on risky choice of slot machine of: (1) neutral sounds paired with winning, (2) casino‐related cues (such as the sound of coins dropping and pictures of dollar signs) and (3) relative payouts. Design: Experimental studies in which participants repeatedly chose between safer and riskier simulated slot machines. Safer slot machines paid the same amount regardless of which symbols lined up. Risky machines paid different amounts depending on which symbols lined up. Effects of initially neutral sounds paired with the best payout were assessed between‐groups (experiment 1a) and within‐participants (experiment 1b). In experiment 2, pairing of casino‐related audiovisual cues with payout was assessed within participants, and cue timing was assessed between groups. Setting: A university research laboratory in Edmonton, Canada. Participants: Undergraduate students (n = 630 across three experiments). Measurements: Preference for riskier over safer machines, preference between machines that differed in cues, payout recall and frequency estimates for payouts. Risky choice was calculated as the proportion of choices of the risky machine when presented with a fixed machine of the same expected value. Findings: In experiment 1a, risky choice was slightly increased by pairing a sound with the best payout compared with pairing the sound with a lower payout ( P  = 0.04, d  = 0.28) but not compared with no sound [ P  = 0.36, d  = 0.13, Bayes factors (BF)10  = 0.22]. In experiment 1b, people did not prefer a machine with a best‐payout sound over one with a lower‐payout sound ( P  = 0.67, d  = 0.03, BF10  = 0.11). Relative payout affected choice: risky choices were higher for high‐ than low‐payout decisions ( P  < 0.001, d  = 0.53). In experiment 2, people preferred machines with casino‐related cues paired with winning ( P  < 0.001, r 2  = 0.11) and cue timing (at choice or concurrently with the win) had no effect ( P  = 0.95, r 2  = 0.0, BF10  = 0.05). Casino‐related cues also enhanced payout memory ( P =  0.013 and 0.006). Cue effects were not specific to risk: people also preferred fixed‐payout machines with casino‐related cues ( P  < 0.001, r 2  = 0.16). Conclusions: In a gambling simulation, student participants chose more risky slot machines when payouts were relatively higher and when casino‐related cues were associated with payouts. Pairing a neutral sound with the best payout did not consistently affect slot machine choice, and the effect of casino cues did not depend on their timing. Casino‐related cues enhanced payout memory.